Pulmonary oedema in the emergency room: what is hidden beyond an apparently common presentation - Patrício, Catarina (BMJ Publishing Group, 2014)
Cardiogenic flash pulmonary oedema is a common and potentially fatal cause of acute respiratory distress. Although it often results from acute decompensated heart failure, abrupt-onset aortic regurgitation can sharply rise cardiac filling pressure and, consequently, pulmonary venous pressure, leading to rapid fluid accumulation in the interstitial and alveolar spaces. We report a case of a 64-year-old woman admitted to the emergency department with a flash pulmonary oedema; a careful clinical investigation subsequently revealed a rare aetiology for this ‘common’ presentation. After a detailed auscultation that unmasked a diastolic cardiac murmur, an acute severe aortic insufficiency was further confirmed by echocardiography, showing inflammation and thickening of the entire aorta wall. The patient was submitted to valve replacement surgery, and histological examination, to our surprise, showed features of aortitis, remarkable for the presence of giant cells. A diagnosis of idiopathic aortitis versus inaugural giant cell arteritis was proposed and treatment started with corticosteroids.